Stanford in Turmoil : Campus Unrest, 1966-1972. - Lyman, Richard (Stanford University Press, 2009)
A rare insider's look at Stanford's experience of dramatic political unrest during the late 1960s and early 1970s, during which time the author served as the university's vice president, provost, and then president.